PERBANDINGAN TINGKAT KELELAHAN PADA PASIEN DIABETIC KIDNEY DISEASE DAN HYPERTENSION KIDNEY DISEASE YANG MENJALANI HEMODIALISA DI KOMUNITAS INDONESIA KIDNEY CARE CLUB TAHUN 2020 - Dewi Astri Yulianti (2020)
Chronic kidney disease is a health problem that attacks the kidneys causing decreased in kidney function properly and is characterized by a GFR < 15 ml/min/1,73 m^2. The kidneys are unable to filter well so that it causing uremia. Fatigue is a feeling of physical fatigue due to physical activity carried out without stopping.. This study aims to compare the level of fatigue in patients with diabetic kidney disease and hypertension kidney disease who undergo hemodialysis in the community of Indonesia Kidney Care Club. A design study analytic description with a cross sectional approach. The sample in this study amounted to 52 respondents. The results of the analysis showed no connection between the characteristics of patients including age, gender, education, occupation and hemoglobin levels, because p value >0,05. Then it was found that there was no different of the level of fatigue in patients with diabetic kidney disease and hypertension kidney disease undergoing hemodialysis (p value = 0.187).